Gambaran Pengelolaan Sampah Rumah Tangga melalui Bank Sampah di Kota Pekanbaru - Zukri Afriadi; Husna Yetti; Abdiana Abdiana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Population growth and changes in food consumption patterns in the community have brought social consequences in the form of increasing waste production which is increasingly diverse in terms of volume, type and characteristics of waste. Waste has a negative impact on the environment and health, pollution of river water quality can increase the number of diseases, one of which is diarrheal disease. The way to overcome the impact of waste is to reduce the generation of waste starting from the main source. Pekanbaru City Environment and Hygiene Agency said that the volume of waste generation in Pekanbaru in 2018 is 492.11 tons / day and only 3-5% of waste is managed by the community with the 3R concept (reduce, reuse, recycle). The effort of the city government to overcome the amount of waste generation is by implementing household waste management through a waste bank program. This study aims to see an overview of the management of waste banks in the city of Pekanbaru based on the results of interviews and field observations. Keywords: description; household waste management; waste bank. ABSTRAK Pertumbuhan populasi dan perubahan pola konsumsi makanan di masyarakat telah membawa konsekuensi sosial dalam bentuk peningkatan produksi sampah yang semakin beragam dalam hal volume, jenis dan karakteristik limbah. Sampah berdampak negatif pada lingkungan dan kesehatan, pencemaran kualitas air sungai dapat menambah jumlah penyakit, salah satunya penyakit diare. Cara mengatasi dampak limbah adalah dengan mengurangi timbulan limbah mulai dari sumber utama. Badan Lingkungan Hidup dan Kebersihan Kota Pekanbaru mengatakan bahwa volume timbulan sampah di Pekanbaru pada tahun 2018 adalah 492.11 ton / hari dan hanya 3-5% limbah dikelola oleh masyarakat dengan konsep 3R (reduce, reuse, recycle). Upaya pemerintah kota untuk mengatasi jumlah timbulan sampah adalah dengan menerapkan pengelolaan limbah rumah tangga melalui program bank sampah. Penelitian ini bertujuan untuk melihat gambaran umum pengelolaan bank sampah di Kota Pekanbaru berdasarkan hasil wawancara dan observasi lapangan Kata kunci: gambaran; pengelolaan sampah rumah tangga; bank sampah.